FEATURES OF STATISTICAL COUNT OF SUPPLIES AND PROGNOSTICATION OF INDEXES OF DEVELOPMENT OF OILFIELD ON A LATE STAGE - Бойко, Василь Степанович; Лагуш, Роман Федорович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The task of improvement of methods of statistical count of supplies and prognostication of indexes of development of oilfield is decided on a late stage. It is suggested to take complex three methodical approaches and method of "voting", to estimate drenovate stock petroleums, which are on one mining hole, and consequently to conduct estimation of necessary amount of extractive mining holes for the selection of the appraised extractive supplies of petroleum after the method of "voting" (whether ratified DCZ). A new method of prognostication of booty of petroleum is offered on the late stage of development of deposit, and a new description is applied for prognostication of water-beaten products of mining holes, that does possible at the booty of petroleum to get the forecast booty of liquid and water. The example of application of the given methods is resulted in relation to the concrete bed of oilfield.